2017
DOI: 10.3171/2016.6.jns16822
|View full text |Cite
|
Sign up to set email alerts
|

Performing concurrent operations in academic vascular neurosurgery does not affect patient outcomes

Abstract: OBJECTIVE Concurrent surgeries, also known as "running two rooms" or simultaneous/overlapping operations, have recently come under intense scrutiny. The goal of this study was to evaluate the operative time and outcomes of concurrent versus nonconcurrent vascular neurosurgical procedures. METHODS The authors retrospectively reviewed 1219 procedures performed by 1 vascular neurosurgeon from 2012 to 2015 at the University of California, San Francisco. Data were collected on patient age, sex, severity of illness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…Although this study was matched case by case in a statistical model, relative case numbers within each specialty were small, and no conclusions can be made about specific case types from this analysis. Zygourakis et al 23 published their single-center, single-provider experience with 1219 vascular neurosurgery cases at the University of California, San Francisco, with results similar to those of earlier studies-variations in case complexity were present between overlapping and nonoverlapping cases, but no evidence of worse outcomes with overlapping surgery was identified in a multivariate analysis. We sought to evaluate the practice of overlapping surgery in a more homogeneous cohort of patients undergoing microsurgical clipping of an acutely ruptured aneurysm with data from a prospective, randomized trial.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although this study was matched case by case in a statistical model, relative case numbers within each specialty were small, and no conclusions can be made about specific case types from this analysis. Zygourakis et al 23 published their single-center, single-provider experience with 1219 vascular neurosurgery cases at the University of California, San Francisco, with results similar to those of earlier studies-variations in case complexity were present between overlapping and nonoverlapping cases, but no evidence of worse outcomes with overlapping surgery was identified in a multivariate analysis. We sought to evaluate the practice of overlapping surgery in a more homogeneous cohort of patients undergoing microsurgical clipping of an acutely ruptured aneurysm with data from a prospective, randomized trial.…”
Section: Discussionmentioning
confidence: 54%
“…In teaching institutions, overlapping cases are also associated with more resident involvement and graduated autonomy for surgeons in training, which many believe represents an invaluable learning opportunity. 4,9,23 However, recent reports questioning the safety of overlapping surgery have required surgeons and institutions to address this strategy to ensure that the best possible care is being offered to patients. 16,21 Few studies have been performed on this subject to date, and recent changes in practice have been driven by anecdotal reports of surgical complications in overlapping or concurrent cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, in a number of recent studies, resident involvement in neurosurgical care has not been found to impact patient outcomes. 3,11,17 We aimed to qualitatively assess the number of VP shunt-associated hemorrhagic complications with respect to chief resident coverage periods to assess safety of resident involvement for this patient subset.…”
mentioning
confidence: 99%
“…On 2 or 3 days each week, Dr. Wilson would perform up to 8 major cases each day, by virtue of his operating in 3 different rooms each day. Overlapping or simultaneous surgery has become an important topic in the recent neurosurgical literature, 2,3,8 but it is probably fair to say that Dr. Wilson was one of the earliest proponents and masters of this approach to neurosurgical cases.…”
mentioning
confidence: 99%